The Effect of Price Perception, Existence and Trust of a Brand on Consumers' Decisions to Use Lublyu Wedding Organizer Services - Nadia Maulidah Nurul Robi Zain; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine Price Perception, Existence and Brand Trust on Consumer Decisions to Use Lublyu Wedding Organizer Services. This data uses primary data in the form of distributing questionnaires to clients who have used the services of a lublyu wedding organizer for 44 respondents, using the perposive sampling method. The data analysis technique uses the SmartPLS 3.3.8 program. This shows that perceived price and existence do not have a positive and significant effect on consumer decisions, while the brand trust variable has a positive and significant effect on satisfaction. The coefficient of determination (Adjusted R Square) is 0.864, this indicates that the perception of price, existence and brand trust contributes 86.4% to consumer decisions while the remaining 13.6% is influenced by variables not examined.